Production process of environment-friendly PP synthetic paper transparent PET bottom adhesive sticker composite material
By adding specific modified quadruple-shaped zinc oxide whiskers and polyarylsulfone to the self-adhesive material, and preparing an isolation layer and adhesive layer with specific components, the problem of insufficient UV resistance and high temperature resistance of traditional self-adhesive materials is solved, and efficient UV printing and good bonding performance is achieved.
Patent Information
- Application Number
- CN202510155803.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-06-24
AI Technical Summary
The poor UV resistance performance of traditional self-adhesive materials has limited applications in high-end packaging and labeling fields. At the same time, their high-temperature resistance is insufficient, resulting in problems of aging, deformation and reduced viscosity during storage.
By adding tetrapod zinc oxide whiskers treated with goose deoxycholic acid and polyaryl sulfone treated with carboxymethyl cellulose, and crosslinking in a high temperature melting state, the ultraviolet light resistance and peel strength of the self-adhesive adhesive were improved; at the same time, the isolation layer was prepared by carboxylated vapor-phase silica, polylactic acid, hydroxypropyl methyl cellulose and nano-zinc oxide particles to improve the ultraviolet and heat resistance of the self-adhesive adhesive; in the preparation of the adhesive layer, the amount of reaction raw materials and system viscosity are adjusted to increase the initial viscosity and stickyness of the self-adhesive adhesive.
The high UV resistance of self-adhesive adhesives in the UV printing process is achieved, which improves peel strength and reduces the residual glue rate; at the same time, the high temperature resistance of self-adhesive adhesives is enhanced, so that they still maintain good bonding performance after thermal aging and ultraviolet aging.
Smart Images

Figure CN120192713A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of self - adhesive, and specifically to a production process of an environment - friendly PP synthetic paper transparent PET - based self - adhesive composite material. Background Art
[0002] Self - adhesive composite materials are widely used in fields such as packaging and labels. They have good strength, tear resistance, flexibility, high transparency, and good chemical corrosion resistance. Using self - adhesive composite materials for packaging can not only achieve exquisite printing but also be easily pasted on various - shaped packaging containers. In the label field, whether it is food, daily chemical products, or electronic products, etc., labels that are firm, beautiful, and can adapt to different environments are required.
[0003] UV printing is an efficient and environment - friendly printing technology and is widely used in the printing of traditional self - adhesive composite materials. However, due to the poor ultraviolet - irradiation resistance of traditional self - adhesive materials, they cannot meet the requirements of high - quality printing, which limits the application of self - adhesives in high - end packaging and label fields. During storage, due to long - term ultraviolet irradiation of self - adhesives, poor ultraviolet resistance will cause the self - adhesives to age, become brittle and hard, lose their original flexibility and adhesiveness, and the adhesiveness decreases. The adhesiveness of self - adhesives mainly depends on their chemical structure and intermolecular forces, and ultraviolet rays will damage these structures and forces, resulting in a decrease in adhesiveness and an inability to firmly adhere to the surface of objects, causing the label to fall off. High - temperature situations are inevitable during storage. Self - adhesive composite materials with poor high - temperature resistance will have phenomena such as deformation, degumming, a decrease in peel strength, and a high amount of residual glue. Their physical and chemical properties will significantly decline, reducing their service life and scope of use. The existing technology improves the performance of self - adhesives by adding temperature - resistant substances such as inorganic fillers, but the added materials have poor compatibility with the system, further reducing the performance of self - adhesives.
[0004] Therefore, a production process of an environment - friendly PP synthetic paper transparent PET - based self - adhesive composite material is proposed. Summary of the Invention
[0005] The purpose of the present invention is to provide a production process of an environment - friendly PP synthetic paper transparent PET - based self - adhesive composite material. By adding four - legged zinc oxide whiskers treated with chenodeoxycholic acid and polyarylsulfone treated with carboxymethyl cellulose, PP synthetic paper is obtained; by reacting polyurethane, acrylate, and flexible groups, an adhesive layer is obtained; by scraping and coating an adhesion promoter prepared on one side of the PP synthetic paper, and then compounding it with a release layer and the adhesive layer, and finally thermally pressing and compounding it with an etched transparent PET base to obtain a self - adhesive composite material, controlling the preparation thickness of each layer and adjusting the raw materials and methods of production; after the self - adhesive composite material undergoes thermal aging and ultraviolet aging, it has good peeling performance and strong bonding performance.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a production process for an environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material. The production process is as follows: After cleaning a 19 - 30 μm transparent PET film with deionized water, soak it in an etching solution at 30 °C for 3 - 5 min, then wash and dry to obtain an etched transparent PET film; scrape and coat 10 - 15 μm of an adhesion promoter on one side of the PP synthetic paper, then arrange the release layer on the side of the adhesion promoter, and after fixing, scrape and coat a filling adhesive layer in the voids of the release layer, controlling the thicknesses of the release layer and the adhesive layer to be 10 - 15 μm and 36 - 50 μm respectively, and dry to obtain a composite PP synthetic paper; stack the adhesive layer of the composite PP synthetic paper with the etched transparent PET film, and perform hot pressing and compounding through a compounding machine. The compounding temperature is 80 - 120 °C, the compounding pressure is 0.5 - 2 MPa, and the compounding speed is 5 - 20 m / min. After cooling, cut and package to obtain an environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material;
[0008] The PP synthetic paper is prepared from PP resin, four-legged zinc oxide whiskers treated with chenodeoxycholic acid, polyarylsulfone treated with carboxymethyl cellulose, mica powder, glycerol monostearate, and erucamide;
[0009] The adhesive layer is prepared from (3 - glycidyletherpropyl)-1,1,3,3 - tetramethyldisiloxane, 1,4 - butanediol divinyl ether, dodecene - 1 - yl succinic acid, polyvinyl alcohol, isophorone diisocyanate, carboxymethyl cellulose, and dodecyl glycoside;
[0010] The release layer is prepared from carboxylated fumed silica, polylactic acid, hydroxypropyl methylcellulose, and nano - zinc oxide particles.
[0011] Preferably, the preparation method of the PP synthetic paper is as follows: Dry the PP resin at 100 °C for 3 h; add 100 parts of the dried PP resin to a high - speed mixer, start stirring, and set the stirring speed to 500 rpm; sequentially add 5 - 10 parts of four - legged zinc oxide whiskers treated with chenodeoxycholic acid, 3 - 8 parts of polyarylsulfone treated with carboxymethyl cellulose, 2 - 5 parts of mica powder, 1 - 3 parts of glycerol monostearate, and 0.5 part of erucamide, and continue stirring for 15 min to fully mix all the materials evenly; add the mixed materials to a twin - screw extruder, melt - extrude and pelletize, and then cast into a film and biaxially stretch to obtain the PP synthetic paper.
[0012] Preferably, the preparation method of chenodeoxycholic acid-treated tetrapod-like zinc oxide whiskers is as follows: Take tetrapod-like zinc oxide whiskers with an aspect ratio of 10 - 30, clean and dry them to obtain pretreated tetrapod-like zinc oxide whiskers; dissolve chenodeoxycholic acid in absolute ethanol to obtain a chenodeoxycholic acid solution with a mass fraction of 5%; add the pretreated tetrapod-like zinc oxide whiskers to the chenodeoxycholic acid solution, and the mass fraction ratio of the pretreated tetrapod-like zinc oxide whiskers to the chenodeoxycholic acid solution is 1:5 - 1:10. Stir at 300 rpm at room temperature for 3 h. After sufficient stirring, filter the mixture, wash the filter residue with absolute ethanol 3 times, and finally dry it in an oven at 60 °C for 6 h to obtain chenodeoxycholic acid-treated tetrapod-like zinc oxide whiskers.
[0013] Preferably, the preparation method of carboxymethyl cellulose-treated polysulfone is as follows: Slowly add 1 part of carboxymethyl cellulose to deionized water to prepare an aqueous carboxymethyl cellulose solution with a mass fraction of 3%; add 10 parts of polysulfone to N-methylpyrrolidone and stir at a temperature of 50 °C to prepare a polysulfone solution with a mass fraction of 10%; slowly drip the aqueous carboxymethyl cellulose solution into the polysulfone solution; the mass fraction ratio of carboxymethyl cellulose to polysulfone is 1:10 - 1:20; stir at a speed of 1000 rpm at a temperature of 70 °C for 3 h to obtain a mixture; slowly pour the mixture into deionized water, filter, wash it with deionized water 4 times, and finally dry it to obtain carboxymethyl cellulose-treated polysulfone.
[0014] Preferably, the preparation method of the adhesion promoter is as follows: Add 11.4 parts of carboxymethyl cellulose and 29.2 parts of dodecyl glucoside to the reaction system, and at the same time add 0.5 part of concentrated sulfuric acid, 13.5 parts of phenylboronic acid and 500 parts of deionized water. Heat up to 70 °C and react for 4 h. Then adjust the pH to 8.5 and add 11.5 parts of dopamine hydrochloride. Stir at room temperature for 24 h to obtain the adhesion promoter.
[0015] Preferably, the preparation method of the isolation layer is as follows: 4.5 - 6.5 parts of carboxylated fumed silica are dispersed in 100 parts of absolute ethanol, and ultrasonically dispersed for 30 min to obtain a uniform fumed silica suspension; 8 - 15 parts of polylactic acid are completely dissolved in 500 parts of ethylene glycol diacetate to obtain a polylactic acid solution; 2.8 - 4.0 parts of hydroxypropyl methylcellulose are added to 80 parts of deionized water and dissolved at 50 °C to obtain a hydroxypropyl methylcellulose solution; 2.4 - 3.6 parts of nano-zinc oxide particles are dispersed in a mixture of 0.5 part of sodium dodecyl sulfate and 50 parts of deionized water, and ultrasonically dispersed for 1 h to obtain a surface-treated nano-zinc oxide dispersion; the fumed silica suspension is slowly poured into the polylactic acid solution and stirred at 650 rpm for 3 h to obtain a pre-isolation layer liquid; the hydroxypropyl methylcellulose solution is added to the pre-isolation layer liquid and stirred for another 2 h to obtain an intermediate isolation layer liquid; the intermediate isolation layer liquid is rotary evaporated to 30 parts, then 120 parts of absolute ethanol are added thereto, and an isolation layer precursor is obtained by electrospinning; the isolation layer precursor is immersed in the surface-treated nano-zinc oxide dispersion, taken out after soaking for 10 - 18 h, rinsed 3 times with deionized water to remove the unbound nano-zinc oxide particles on the surface, and then vacuum dried at 50 °C for 6 h to obtain an intermediate isolation layer; after the intermediate isolation layer is woven, an isolation layer is formed; the average pore size of the isolation layer is 0.05 - 0.2 mm; the specific surface area of the fumed silica is 350 m 2 / g, and the carboxyl value is 0.8 - 2.0 mmol / g.
[0016] Preferably, the preparation method of the adhesive layer is as follows: The reaction is carried out under nitrogen conditions. 155 - 168 parts of (3-glycidyletherpropyl)-1,1,3,3-tetramethyldisiloxane and 110 - 120 parts of 1,4-butylene glycol vinyl ether are added to 200 parts of a mixed solvent, stirred evenly, 0.1 part of a catalyst is added, stirred for 5 min and then heated to 100 °C, and reacted for 6 h to obtain an addition product; 128 parts of butyl acrylate and 2 parts of azobisisobutyronitrile are added to the addition product, and refluxed for 5 h; cooled to 80 °C, and a mixture of 123 - 132 parts of dodecenyl succinic anhydride and 0.05 part of concentrated sulfuric acid is added continuously. After slowly adding within 30 min, the reaction is carried out at 500 rpm for 3 h to obtain an esterification product; 44 - 60 parts of polyvinyl alcohol and 0.01 part of concentrated sulfuric acid are added to the esterification product, heated to 90 °C, and reacted for 4 h to obtain an adhesive precursor; the temperature of the adhesive precursor is lowered to 60 °C, 108 - 120 parts of isophorone diisocyanate are slowly added dropwise, the dropping time is controlled within 1.5 h, then 0.5 part of triethylamine is added, and the reaction is continued for 5 h to obtain an adhesive intermediate; 11.4 - 13.0 parts of carboxymethyl cellulose and 29.2 - 31.0 parts of dodecyl glycoside are added to the adhesive intermediate, and the mixed solvent is supplemented to make the total number of parts of the system 500. After reacting for 6 h, the obtained product is filtered, washed with deionized water and distilled under reduced pressure to obtain the adhesive layer.
[0017] Preferably, the viscosity of the adhesive layer is 11,000 - 13,000 cps.
[0018] Preferably, the preparation method of the etched transparent PET film is as follows: Take a transparent PET film, wash the surface with deionized water to remove dust and oil, and dry it at 80 °C for 45 min; dissolve concentrated sulfuric acid and dodecyl glucoside in deionized water; the mass concentration of concentrated sulfuric acid in the prepared etching solution is 15%, and the mass concentration of dodecyl glucoside is 1%; immerse the washed and dried transparent PET film in the etching solution, soak it at 30 °C for 3 - 5 min, then take it out, rinse it with deionized water, and dry it at 60 °C for 80 min to obtain the etched transparent PET film.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0020] 1. By using PP resin as the main reaction raw material, modifying the tetrapod-like zinc oxide whiskers with chenodeoxycholic acid, modifying the polyarylsulfone with carboxymethyl cellulose, and adding mica powder, glycerol monostearate, and erucamide at the same time, at the high-temperature molten state, the amino and carboxyl groups in chenodeoxycholic acid and carboxymethyl cellulose crosslink, so that the tetrapod-like zinc oxide whiskers and polyarylsulfone are introduced into the reaction system through chemical bonds, improving the UV resistance effect of the pressure-sensitive adhesive during the UV printing process. In addition, the coefficient of thermal expansion between each layer tends to be consistent, thereby improving the peel strength of the pressure-sensitive adhesive and reducing the residual glue rate.
[0021] 2. By using carboxylated fumed silica, polylactic acid, hydroxypropyl methylcellulose, and nano-zinc oxide particles as reaction raw materials, changing the carboxyl value of the carboxylated fumed silica, and adjusting the soaking time after electrospinning, so that the nano-zinc oxide is connected with other components in a self-assembled manner, and at the same time, the wire meshes of the electrospinning are reasonably arranged, and the average pore diameter of the isolation layer is adjusted, thereby increasing the UV and heat resistance of the pressure-sensitive adhesive composite material.
[0022] 3. By adjusting the dosage of the raw materials for preparing the adhesive layer, using (3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane as the initial reaction raw material, and then reacting with 1,4-butylene glycol vinyl ether, butyl acrylate, dodecenyl succinic acid, polyvinyl alcohol, isophorone diisocyanate, carboxymethyl cellulose, and dodecyl glucoside, so that the above substances react and polymerize to obtain a long-chain molecular adhesive, introducing compounds with structures such as acrylate and polyurethane into the system, and adjusting the system viscosity of the adhesive layer, thereby increasing the initial tack and holding power of the pressure-sensitive adhesive.
[0023] 4. An adhesion promoter is prepared and coated on one side of the PP synthetic paper. The adhesion promoter contains abundant amino and hydroxyl functional groups, thereby promoting its crosslinking with the release layer and the adhesive layer and improving the bonding effect. By subjecting the transparent PET film to surface etching treatment, on the one hand, a good matte visual effect is obtained, and on the other hand, the surface roughness of the PET is increased. The introduced surfactant also improves the surface reactivity of the PP synthetic paper and promotes its adhesion and combination with the release layer and the adhesive layer. By controlling the thickness of each layer, the pressure-sensitive adhesive composite material has good initial tack and holding tack, and at the same time has good high-temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a side sectional view of the environmentally friendly PP synthetic paper transparent PET bottom pressure-sensitive adhesive composite material;
[0025] Figure 2 is a test result graph of the holding tack time of Examples 8-11 and Comparative Examples 18-25 of the present invention.
[0026] In the figure: 1. PP synthetic paper; 2. Adhesion promoter; 3. Release layer; 4. Adhesive layer; 5. Transparent PET bottom. DETAILED DESCRIPTION OF THE INVENTION
[0027] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0028] Please refer to Figures 1 to 2 , the present invention provides a production process for an environmentally friendly PP synthetic paper transparent PET bottom pressure-sensitive adhesive composite material, and the technical solutions are as follows:
[0029] The substance information involved in the present invention is as follows:
[0030] Chenodeoxycholic acid CAS: 474-25-9; Carboxymethyl cellulose CAS: 9000-11-7; Polyphenylene sulfone CAS: 65-49-6; Glycerol monostearate CAS: 31566-31-1; Erucamide CAS: 112-84-5; (3-glycidyl ether propyl)-1,1,3,3-tetramethyldisiloxane CAS: 17980-29-9; 1,4-Butanediol vinyl ether CAS: 3891-33-6; Butyl acrylate CAS: 1 41-32-2; Dodecenylsuccinic acid CAS: 29658-97-7; Isophorone diisocyanate CAS: 4098-71-9; Diethylene glycol butyl ether CAS: 112-34-5; Ethylene glycol diacetate CAS: 111-55-7; Hydroxypropyl methylcellulose CAS: 9004-65-3; Sodium dodecyl sulfate CAS: 151-21-3; Phenylboronic acid CAS: 98-80-6; Dopamine hydrochloride CAS: 62-31-7;
[0031] Dodecyl polyglucoside was purchased from BASF AG; PP resin and D80 solvent oil were purchased from China Petrochemical Corporation; tetrapod zinc oxide whiskers were purchased from Sichuan Xinju Emerging New Materials Technology Co., Ltd.; mica powder was purchased from Chuzhou Wanqiao Mineral New Materials Co., Ltd.; Speier catalyst was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; polylactic acid was purchased from Zhejiang Hisun Biomaterials Co., Ltd.; nano zinc oxide particles were purchased from Xianfeng Nanotechnology Co., Ltd.; transparent PET film was purchased from Sichuan Dongcai Technology Group Co., Ltd. It should be noted that the "parts" in the present invention are all "parts by mass"; the solvents used are all environmentally friendly solvents.
[0032] Example 1
[0033] 11.4 parts of carboxymethyl cellulose and 29.2 parts of dodecyl glucoside were added to the reaction system, and 0.5 parts of concentrated sulfuric acid, 13.5 parts of phenylboric acid and 500 parts of deionized water were added at the same time, the temperature was raised to 70°C, and the reaction was performed for 4 hours, and then the pH was adjusted to 8.5, and 11.5 parts of dopamine hydrochloride were added, and the mixture was stirred at room temperature for 24 hours to obtain an adhesion promoter;
[0034] Apply a 12-μm adhesion promoter on one side of the PP synthetic paper with a thickness of 40 μm. Then, arrange the release layer on the side with the adhesion promoter. After drying and fixing at 80°C for 8 minutes, scrape and fill the adhesive layer in the voids of the release layer, controlling the thicknesses of the release layer and the adhesive layer to be 10 μm and 42 μm respectively. Dry at 70°C for 80 minutes to obtain the composite PP synthetic paper. Stack the adhesive layer of the composite PP synthetic paper with the etched transparent PET film and perform hot pressing and lamination through a laminator. Control the lamination temperature at 100°C, the lamination pressure at 1.5 MPa, and the lamination speed at 15 m / min. Then, cool, cut, and package to obtain the environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material, whose structure is as Figure 1 shown, consisting of a five-layer structure. From top to bottom, the structure is successively the PP synthetic paper 1, the adhesion promoter 2, the release layer 3, the adhesive layer 4, and the transparent PET bottom 5.
[0035] The PP synthetic paper is produced from Preparation Example 1; the adhesive layer is produced from Preparation Example 2; the release layer is produced from Preparation Example 3; the etched transparent PET film is produced from Preparation Example 4.
[0036] Preparation Example 1
[0037] Dry the PP resin at 100°C for 3 h to remove moisture. Add 100 parts of the dried PP resin (melt flow rate of 8 g / 10 min) to a high-speed mixer, start stirring, and set the stirring speed at 500 rpm. Successively add 6 parts of four-legged zinc oxide whiskers treated with chenodeoxycholic acid, 3 parts of polyarylsulfone treated with carboxymethyl cellulose, 2 parts of mica powder, 2 parts of glycerol monostearate, and 0.5 part of erucamide, and continue stirring for 15 min to fully mix all the materials evenly. Add the mixed materials to a twin-screw extruder for melt extrusion and pelletization. The temperature of zone 1 is 180°C, the temperature of zone 2 is 200°C, the temperature of zone 3 is 210°C, the temperature of the die head is 230°C, and the screw speed is 150 rpm. Add the extruded pellets to a single-screw extruder for casting into a film, and finally perform biaxial stretching. Control the stretching temperature at 120°C and the stretching ratio at 4 times. Then, perform transverse stretching, control the stretching temperature at 140°C, and the stretching ratio at 4 times to obtain the PP synthetic paper. The longitudinal stretching time is 2 s, and the transverse stretching time is 4 s;
[0038] The preparation method of chenodeoxycholic acid-treated tetrapod-like zinc oxide whiskers is as follows: Take tetrapod-like zinc oxide whiskers (aspect ratio is 15), wash them repeatedly with deionized water to remove surface impurities, and then dry them in an oven at 80 °C for 3 h until constant weight to obtain pretreated tetrapod-like zinc oxide whiskers; dissolve chenodeoxycholic acid in absolute ethanol to obtain a chenodeoxycholic acid solution with a mass fraction of 5%; add the pretreated tetrapod-like zinc oxide whiskers to the chenodeoxycholic acid solution, and the mass ratio of the pretreated tetrapod-like zinc oxide whiskers to the chenodeoxycholic acid solution is 1:8. Stir at 300 rpm at room temperature for 3 h. After sufficient stirring, filter the mixture, wash the filter residue with absolute ethanol 3 times, and finally dry it in an oven at 60 °C for 6 h to obtain chenodeoxycholic acid-treated tetrapod-like zinc oxide whiskers.
[0039] Slowly add 1 part of carboxymethyl cellulose to deionized water, and stir at a speed of 300 rpm in a water bath at 60 °C to prepare an aqueous carboxymethyl cellulose solution with a mass fraction of 3%; add 10 parts of polyarylsulfone to N-methylpyrrolidone and stir at a temperature of 50 °C to prepare a polyarylsulfone solution with a mass fraction of 10%; slowly drop the aqueous carboxymethyl cellulose solution into the polyarylsulfone solution, and the mass ratio of carboxymethyl cellulose to polyarylsulfone is 1:20. Stir at a speed of 1000 rpm at a temperature of 80 °C for 3 h to obtain a mixture; slowly pour the mixture into a large amount of deionized water to precipitate carboxymethyl cellulose-treated polyarylsulfone; then filter, wash with deionized water 4 times to remove organic solvents and unreacted carboxymethyl cellulose, and finally dry to obtain carboxymethyl cellulose-treated polyarylsulfone.
[0040] Preparation Example 2
[0041] The reaction is carried out under nitrogen. 162 parts of (3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane and 116 parts of 1,4-butanediol vinyl ether are added to 200 parts of a mixed solvent. After stirring evenly, 0.1 part of Speier catalyst is added. After stirring for 5 min, the temperature is raised to 100 °C, and the reaction is carried out for 6 h to obtain an addition product. At this time, the conversion rate of (3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane is 97.5%; then 128 parts of butyl acrylate and 2 parts of azobisisobutyronitrile are added, and the reflux reaction is carried out for 5 h; the temperature is lowered to 80 °C, and a mixed solution of 126 parts of dodecenyl succinic acid and 0.05 part of concentrated sulfuric acid is continuously added. After slowly adding it within 30 min, the reaction is carried out for 3 h at a rotation speed of 500 rpm to obtain an esterification product; 44 parts of polyvinyl alcohol (degree of polymerization 1750, degree of alcoholysis 99%) and 0.01 part of concentrated sulfuric acid are added to the esterification product, and the temperature is raised to 90 °C, and the reaction is carried out for 4 h to obtain a precursor of the adhesive; the temperature of the precursor of the adhesive is lowered to 60 °C, and 111 parts of isophorone diisocyanate are slowly added dropwise, and the dropping time is controlled within 1.5 h. Then 0.5 part of triethylamine is added, and the reaction is continued for 5 h to obtain an adhesive intermediate; 11.4 parts of carboxymethyl cellulose and 29.2 parts of dodecyl glucoside are added to the adhesive intermediate, and the mixed solvent is supplemented to make the total number of parts of the system 500 parts. After reacting for 6 h, the obtained product is filtered, washed with deionized water and distilled under reduced pressure to obtain an adhesive layer; the viscosity of the system reaches 11000 cps; the mixed solvent is obtained by mixing diethylene glycol butyl ether and D80 solvent oil according to a volume ratio of 1:1.
[0042] Preparation Example 3
[0043] 5 parts of carboxylated fumed silica (specific surface area 350 m 2( / g, carboxyl value 1.5 mmol / g) was dispersed in 100 parts of absolute ethanol, and ultrasonic dispersion was carried out for 30 min to obtain a uniform suspension of fumed silica; 10 parts of polylactic acid was completely dissolved in 500 parts of ethylene glycol diacetate to obtain a polylactic acid solution; 3 parts of hydroxypropyl methylcellulose was added to 80 parts of deionized water and dissolved at 50 °C to obtain a hydroxypropyl methylcellulose solution; 3 parts of nano-zinc oxide particles were dispersed in a mixed solution of 0.5 part of sodium dodecyl sulfate and 50 parts of deionized water, and ultrasonic dispersion was carried out for 1 h to obtain a surface-treated nano-zinc oxide dispersion; the fumed silica suspension was slowly poured into the polylactic acid solution, and stirring was carried out at 650 rpm for 3 h to obtain a pre-layer solution for the isolation layer; the hydroxypropyl methylcellulose solution was added to the pre-layer solution for the isolation layer, and stirring was continued for 2 h to obtain an intermediate solution for the isolation layer; the intermediate solution for the isolation layer was rotary evaporated to 30 parts, and then 120 parts of absolute ethanol was added thereto, and electrospinning was carried out to obtain a precursor for the isolation layer; the precursor for the isolation layer was soaked in the surface-treated nano-zinc oxide dispersion, taken out after soaking for 12 h, rinsed 3 times with deionized water to remove the unbound nano-zinc oxide particles on the surface, and then vacuum dried at 50 °C for 6 h to obtain an intermediate for the isolation layer; after the intermediate for the isolation layer was woven, an isolation layer was formed; the average pore size of the isolation layer was 0.15 mm; the specific surface area of fumed silica was 350 m 2 / g, carboxyl value 0.8 - 2.0 mmol / g.
[0044] Preparation Example 4
[0045] The surface of a 25-μm transparent PET film was cleaned with deionized water to remove dust and oil, and dried at 80 °C for 45 min; concentrated sulfuric acid and dodecyl glycoside were dissolved in deionized water to prepare an etching solution with a mass concentration of 15% for concentrated sulfuric acid and a mass concentration of 1% for dodecyl glycoside; the transparent PET film was soaked in the etching solution, soaked at 30 °C for 5 min, then taken out, rinsed with a large amount of deionized water, and dried at 60 °C for 80 min to obtain an etched transparent PET film.
[0046] Examples 2 - 4
[0047] Different from Example 1, the preparation method of the PP synthetic paper was changed, as shown in Table 1 specifically. Wherein A is four-legged zinc oxide whiskers treated with chenodeoxycholic acid; B is polyarylsulfone treated with carboxymethyl cellulose; the two substances in A are pretreated four-legged zinc oxide whiskers and chenodeoxycholic acid solution; the two substances in B are carboxymethyl cellulose and polyarylsulfone.
[0048] Comparative Example 1
[0049] Different from Example 1, four-legged zinc oxide whiskers treated with chenodeoxycholic acid were not added.
[0050] Comparative Example 2
[0051] Different from Example 1, the tetrapod-like zinc oxide whiskers are not treated with chenodeoxycholic acid.
[0052] Comparative Example 3
[0053] Different from Example 1, the aspect ratio of the tetrapod-like zinc oxide whiskers is 60.
[0054] Comparative Example 4
[0055] Different from Example 1, polyarylsulfone treated with carboxymethyl cellulose is not added.
[0056] Comparative Example 5
[0057] Different from Example 1, the polyarylsulfone is not treated with carboxymethyl cellulose.
[0058] Comparative Example 6
[0059] Different from Example 1, mica powder is not added.
[0060] Comparative Example 7
[0061] Different from Example 1, glycerol monostearate is not added.
[0062] Comparative Example 8
[0063] Different from Example 1, erucamide is not added.
[0064] Table 1 Preparation method of PP synthetic paper
[0065]
[0066] Experimental Example 1
[0067] The environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite materials prepared in Examples 1-4 and Comparative Examples 1-8 were subjected to UV printing. After thermal aging and ultraviolet aging, the peel strength and residual glue rate of the self-adhesive composite materials were tested. The peel strength was carried out with reference to GB / T 2792-2014 "Test method for peel strength of adhesive tapes"; at the same time, the peel strength and residual glue rate of the materials before aging in Example 3 and Comparative Example 1 were tested. The final test results are shown in Table 2; the thermal aging was carried out at 120 °C for 24 h, and the ultraviolet aging was carried out by irradiating with a 365 nm ultraviolet lamp for 24 h.
[0068] Table 2 Test results of peel strength and residual glue rate
[0069]
[0070]
[0071] The pressure-sensitive adhesive composite material prepared by the present invention has a peel strength of 3.86 - 4.08 N / cm and a residual adhesive rate of 0.42% - 0.61% under the conditions of Examples 1 - 4; before aging, the peel strength of Example 3 is 4.20 N / cm and the residual adhesive rate is 0.56%; before aging, the peel strength of Comparative Example 1 is 3.72 N / cm and the residual adhesive rate is 1.14%; under the conditions of Comparative Examples 1 - 8, the peel strength is 3.15 - 3.80 N / cm and the residual adhesive rate is 1.34% - 1.92%. By treating the tetrapod-shaped zinc oxide whiskers with chenodeoxycholic acid and treating the polyarylsulfone with carboxymethyl cellulose, under the state of high-temperature melting, chemical reactions occur between the carboxyl group and the hydroxyl group, thereby introducing the tetrapod-shaped zinc oxide whiskers and the polyarylsulfone into the PP material. After cross-linking with the PP resin molecules, they are dispersed in the lamellae of mica powder. By adjusting the dosage of the raw materials for preparing the PP synthetic paper, the pressure-sensitive adhesive composite material has a high peel strength and a low residual adhesive rate; the addition of the tetrapod-shaped zinc oxide whiskers can reduce the expansion coefficient of PP. In addition, the aspect ratio of the tetrapod-shaped zinc oxide whiskers is limited, so as to better restrict the thermal movement of the PP molecular chains; when the temperature rises, the expansion of the PP molecular chains is hindered by the whiskers, so that the thermal expansion coefficient of the material is reduced, and the whiskers can form a more continuous heat conduction channel in the PP material, which is beneficial to the conduction and dispersion of heat, further reducing the non-uniformity of thermal expansion, reducing the expansion coefficient, making the expansion coefficients of PP and other components of the environmentally friendly PP synthetic paper transparent PET bottom pressure-sensitive adhesive composite material consistent, thereby avoiding inconsistent expansion coefficients of each part, reducing the peel strength, and at the same time avoiding glue overflow and reducing the residual adhesive rate. The mica powder has a flaky crystal structure. When it is uniformly dispersed in the PP matrix, it generates tiny barriers. These lamellae limit the free movement and stretching of the PP molecular chains, making the activity space of the PP molecular chains smaller during thermal movement, thereby reducing the volume expansion of PP when the temperature changes. At the same time, the addition of mica powder forms more heat conduction channels in the PP. When the PP is heated, the heat can be conducted out faster through the mica powder, making the temperature distribution inside the PP more uniform; the flaky structure of the mica powder has good reflection and scattering effects on ultraviolet rays; the polyarylsulfone molecular chain contains a rigid aromatic ring structure, and these aromatic ring structures make the polyarylsulfone molecular chain have high rigidity and regularity; when the polyarylsulfone is blended with the PP, certain interactions will occur between the polyarylsulfone molecular chain and the PP molecular chain, such as van der Waals forces and hydrogen bonds, etc.; these interactions limit the thermal movement of the PP molecular chains, making the PP molecular chains not easily expand freely when heated; the formed rigid network structure can effectively disperse and transfer stress and inhibit the expansion deformation of the PP; the electron cloud on the aromatic ring of the polyarylsulfone will undergo a transition after absorbing the energy of ultraviolet rays, converting the energy of the ultraviolet rays into the internal energy of the molecule, and then emitting it in the form of heat.For Comparative Example 1, the four-legged zinc oxide whiskers treated without chenodeoxycholic acid have reduced ultraviolet resistance and increased expansion performance of the pressure-sensitive adhesive. The peel strength is lower than that of Example 1, and the residual glue rate is increased; for Comparative Examples 2 and 5, no modification treatment is carried out, and the compatibility of the components with the system is poor, resulting in a decline in the performance of the pressure-sensitive adhesive; for Comparative Example 3, the aspect ratio of the four-legged zinc oxide whiskers is too high, the constraint ability for PP is relatively high, and the entanglement of PP molecules is serious, thus leading to a decline in the performance of the pressure-sensitive adhesive; for Comparative Example 4, polyarylsulfone treated without carboxymethyl cellulose has a lower peel strength than that of Example 1, and the residual glue rate is increased; for Comparative Example 6, without adding mica powder, the tolerance to ultraviolet and high temperature decreases; for Comparative Examples 7 and 8, without adding glycerol monostearate and erucamide respectively, the performance of the pressure-sensitive adhesive declines.
[0072] Examples 5 - 8
[0073] Different from Example 3, the preparation method of the isolation layer is changed, as shown in Table 3 specifically.
[0074] Table 3 Preparation method of the isolation layer
[0075]
[0076] Comparative Example 9
[0077] Different from Example 3, the carboxyl value of the carboxylated fumed silica is 0.1 mmol / g.
[0078] Comparative Example 10
[0079] Different from Example 3, no carboxylated fumed silica is added.
[0080] Comparative Example 11
[0081] Different from Example 3, no polylactic acid is added.
[0082] Comparative Example 12
[0083] Different from Example 3, no hydroxypropyl methylcellulose is added.
[0084] Comparative Example 13
[0085] Different from Example 3, no nano-zinc oxide is added.
[0086] Comparative Example 14
[0087] Different from Example 3, the soaking time is 2 h.
[0088] Comparative Example 15
[0089] Different from Example 3, no isolation layer is added.
[0090] Comparative Example 16
[0091] Different from Example 3, the average pore diameter is 50 mm.
[0092] Comparative Example 17
[0093] Different from Example 3, the raw material for preparing the PP synthetic paper is only PP resin.
[0094] Experimental Example 2
[0095] The environmentally friendly PP synthetic paper transparent PET base self-adhesive composites prepared in Examples 3, 5 - 8 and Comparative Examples 9 - 17 were subjected to tests of peel strength and residual glue rate after thermal aging and ultraviolet aging. In addition, the peel strength and residual glue rate of the self-adhesive composites of Example 8 and Comparative Example 15 before aging were tested. The final test results are shown in Table 4.
[0096] Table 4 Results of peel strength and residual glue rate of Examples 3, 5 - 8 and Comparative Examples 9 - 17
[0097]
[0098] The pressure-sensitive adhesive composite material obtained in the present invention has a peel strength of 4.08 - 4.32 N / cm and a residual adhesive rate of 0.32% - 0.61% under the conditions of Examples 3, 5 - 8; for the pressure-sensitive adhesive composite material of Example 8, the peel strength before aging is 4.40 N / cm and the residual adhesive rate is 0.32%; for the pressure-sensitive adhesive composite material of Comparative Example 15, the peel strength before aging is 3.29 N / cm and the residual adhesive rate is 2.16%. Zinc oxide particles are bonded to the components in the system by self-assembly. Among them, the ends of the polylactic acid molecular chains contain hydroxyl and carboxyl groups. Due to lattice defects and other reasons on the surface of nano-zinc oxide, some zinc atoms or oxygen atoms are exposed, having a certain charge distribution. The oxygen atom in the carboxyl group of polylactic acid has a relatively large electronegativity and will attract the positively charged zinc atoms on the surface of nano-zinc oxide to form an electrostatic interaction; at the same time, the hydrogen atoms in the hydroxyl and carboxyl groups, due to electropositivity, can form a weak hydrogen bond with the oxygen atoms on the surface of nano-zinc oxide; the charge distribution on the surface of nano-zinc oxide can interact with the polarity of the ester group to generate an electrostatic attraction, and at the same time this polar interaction will also contribute to the van der Waals force to enhance the van der Waals force between nano-zinc oxide and polylactic acid; the charge on the surface of nano-zinc oxide can generate an electrostatic attraction with the oxygen atom of the hydroxyl group, and the hydrogen atom can also form a hydrogen bond with the oxygen atom on the surface of nano-zinc oxide, so that the two are combined together through electrostatic interaction and a weak interaction similar to hydrogen bond. Nano-zinc oxide simultaneously generates an electrostatic interaction with the methoxy and hydroxypropoxy groups in hydroxypropyl methylcellulose; there are a large number of silanol groups on the surface of fumed silica. The oxygen atoms in the silanol groups can attract the zinc atoms on the surface of nano-zinc oxide through electrostatic interaction, and at the same time the hydrogen atoms in the silanol groups can also form a hydrogen bond with the oxygen atoms on the surface of nano-zinc oxide; the above substances act synergistically to promote the assembly and combination of zinc oxide onto the precursor of the isolation layer; in Examples 3, 5 - 8, by adjusting the dosage of substances, the carboxyl value, soaking time and line width are adjusted, so that the pressure-sensitive adhesive composite material has a high peel strength and residual adhesive rate.The fumed silica in Comparative Example 9 has a low carboxyl content, which cannot react with the hydroxyl groups on the surface of the PP synthetic paper, nor can it be connected to carboxymethyl cellulose and dodecyl glucoside in the adhesive layer through chemical bonds. As a result, the connectivity with the adhesive layer and the PP synthetic paper is reduced, leading to a decrease in peel strength and an increase in the residual glue rate. In Comparative Examples 10 - 12, carboxylated fumed silica, polylactic acid, and hydroxypropyl methylcellulose are not added respectively, resulting in a decline in heat resistance and a reduction in the crosslinking degree of the system, as well as a decrease in heat aging performance, thus reducing the performance of the pressure-sensitive adhesive. In Comparative Example 13, nano-zinc oxide is not added, resulting in a decline in the performance of UV aging resistance. In Comparative Example 14, the soaking time is too short, and the zinc oxide is not completely self-assembled, so the UV aging resistance effect is reduced. In Comparative Example 15, the release layer is not added, which on the one hand reduces the tolerance to heat aging and UV aging, and on the other hand, the ink for UV printing easily penetrates into the adhesive, thus reducing the bonding performance of the adhesive. In Comparative Example 16, the average pore diameter is too large, while the designs of Examples 3, 5 - 8 can reduce the influence of atmospheric pressure on the bonding surface during lamination, provide a good exhaust channel, thereby increasing the peel strength and reducing the residual glue rate. In Comparative Example 17, the raw material for preparing the PP synthetic paper is only PP resin, and the carboxyl groups of the release layer cannot react with the chemical groups of the PP synthetic paper, resulting in a decline in the performance of the pressure-sensitive adhesive.
[0099] Examples 9 - 11
[0100] Different from Example 8, the preparation method of the adhesive layer is changed, as shown in Table 5 specifically.
[0101] Table 5 Preparation Method of the Adhesive Layer
[0102]
[0103] Comparative Example 18
[0104] Different from Example 8, (3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane is not added.
[0105] Comparative Example 19
[0106] Different from Example 8, 1,4-butanediol vinyl ether is not added.
[0107] Comparative Example 20
[0108] Different from Example 8, dodecenyl succinic anhydride is not added.
[0109] Comparative Example 21
[0110] Different from Example 8, the addition amount of polyvinyl alcohol is 22 parts, and the dosage of isophorone diisocyanate is 121 parts.
[0111] Comparative Example 22
[0112] Different from Example 8, carboxymethyl cellulose was not added.
[0113] Comparative Example 23
[0114] Different from Example 8, dodecyl glucoside was not added.
[0115] Comparative Example 24
[0116] Different from Example 8, the system viscosity was 8000 cps.
[0117] Comparative Example 25
[0118] Different from Example 8, the system viscosity was 15000 cps.
[0119] Experimental Example 3
[0120] The environmentally friendly PP synthetic paper transparent PET bottom pressure-sensitive adhesive composite materials prepared in Examples 8-11 and Comparative Examples 18-25 were subjected to UV printing. After thermal aging and ultraviolet aging, the initial adhesion and holding adhesion were tested. The initial adhesion was tested with reference to GB / T4852-2002 "Test Method for Initial Adhesion of Pressure-Sensitive Adhesive Tapes (Rolling Ball Method)", and the holding adhesion was tested with reference to GB / T4851-2014 "Test Method for Holding Adhesion of Adhesive Tapes". The weight of the weight was 500 g, and the experimental temperature was 25 °C. The test results are shown in Table 6 and Figure 2 as shown. The larger the steel ball number value of the initial adhesion, the better the initial adhesion of the pressure-sensitive adhesive on the surface.
[0121] Table 6 Test Results of Initial Adhesion and Holding Adhesion of Examples 8-11 and Comparative Examples 18-25
[0122]
[0123] For the environmentally friendly PP synthetic paper transparent PET bottom pressure-sensitive adhesive composite materials prepared by the present invention, under the conditions of Examples 8-11, Table 6 shows that the steel ball numbers of the initial adhesion are 10-11, Figure 2The holding tack time is shown as 147 - 165 min; under the conditions of Comparative Examples 18 - 25, the initial tack steel ball numbers are 7 - 13, and the holding tack time is 87 - 181 min. Using (3 - glycidoxypropyl)-1,1,3,3 - tetramethyldisiloxane as the initial reaction raw material, under the action of a catalyst, the silicon - hydrogen bond of (3 - glycidoxypropyl)-1,1,3,3 - tetramethyldisiloxane undergoes an addition reaction with the unsaturated double bond of 1,4 - butanediol vinyl ether. Then, the unsaturated double bond in the introduced 1,4 - butanediol vinyl ether undergoes a polymerization reaction with butyl acrylate. After the epoxy group of (3 - glycidoxypropyl)-1,1,3,3 - tetramethyldisiloxane is ring - opened, it undergoes an esterification reaction with the carboxyl group in dodecenyl succinic acid. The carboxyl group contained in dodecenyl succinic acid then reacts with the hydroxyl group of polyvinyl alcohol, thereby introducing polyvinyl alcohol into the adhesive. The dropped isophorone diisocyanate then reacts with polyvinyl alcohol to introduce a polyurethane group. The unreacted isocyanate groups in isophorone diisocyanate react again with the hydroxyl groups of carboxymethyl cellulose and dodecyl glycoside to form amide bonds, thereby forming an adhesive with long molecular chain segments. In Examples 8 - 11, by adjusting the dosages of the reaction raw materials and the viscosity of the adhesive, the initial tack and holding tack of the environmentally friendly PP synthetic paper transparent PET bottom self - adhesive composite material are good. In Comparative Examples 18 - 20, (3 - glycidoxypropyl)-1,1,3,3 - tetramethyldisiloxane, 1,4 - butanediol vinyl ether, and dodecenyl succinic acid are not added respectively. The siloxane groups, ether bonds, and long - chain alkyl groups endow the system with higher viscosity and adhesiveness. Not adding the above substances will lead to a decrease in the performance of the self - adhesive. In Comparative Example 21, the addition ratio of the hard segment of isophorone diisocyanate is higher than that of the soft segment of polyvinyl alcohol, resulting in an increase in the rigidity of the adhesive. In Comparative Examples 22 and 23, carboxymethyl cellulose and dodecyl glycoside are not added respectively, and the performance of the self - adhesive decreases. The addition of the above substances not only increases the viscosity of the system but also reduces the surface energy of the transparent PET bottom in contact with the adhesive layer, improving the adhesiveness of the system. Not adding them will lead to a decrease in the initial tack and holding tack. In Comparative Examples 24 and 25, too low system viscosity will lead to a decrease in the bonding performance, while too high viscosity is not conducive to the peeling of the self - adhesive composite material, increasing the difficulty of use.
[0124] Examples 12 - 14
[0125] Different from Example 9, the preparation method of the adhesion promoter and the preparation method of the environmentally friendly PP synthetic paper transparent PET bottom self - adhesive composite material are changed, as shown in Table 7 specifically.
[0126] Table 7 Preparation methods of the adhesion promoter and the environmentally friendly PP synthetic paper transparent PET bottom self - adhesive composite material
[0127]
[0128] Comparative Example 26
[0129] Different from Example 9, the adhesion promoter was not scrape-coated.
[0130] Comparative Example 27
[0131] Different from Example 9, the thicknesses of the transparent PET film, adhesion promoter, release layer and adhesive layer were 50 μm, 20 μm, 25 μm and 70 μm, respectively.
[0132] Experimental Example 4
[0133] The initial tack and holding tack of Examples 9, 12 - 14, Comparative Example 26 and Comparative Example 27 were tested, and at the same time, the high-temperature resistance performance was tested. The pressure-sensitive adhesive composite material was pasted on the surface of a stainless steel cylinder with a diameter of 6 cm, and then placed at 100 °C for 1 month to observe whether there was warping of the pressure-sensitive adhesive composite material. The test results are shown in Table 8.
[0134] Table 8 Results of initial tack, holding tack and high-temperature resistance of Examples 9, 12 - 14, Comparative Example 26 and Comparative Example 27
[0135]
[0136] The pressure-sensitive adhesive composite material prepared by the present invention, under the conditions of Examples 9 and 12-14, has an initial tack steel ball number of 11, a holding time of 164-171 minutes, and after high-temperature treatment, there is no peeling off and no warping at the edges; under the conditions of Comparative Examples 26 and 27, the initial tack steel ball number is 7-9, the holding time is 82-110 minutes, and after high-temperature treatment, the warping is serious and it peels off after being touched, and the high-temperature resistance effect is poor. First, an adhesion promoter is prepared. Using carboxymethyl cellulose and dodecyl glucoside as reaction raw materials, after adding phenylboronic acid, under the action of concentrated sulfuric acid, phenylboronic acid undergoes an esterification reaction with the hydroxyl groups in the above raw materials, and the carboxyl group of carboxymethyl cellulose reacts with the hydroxyl group of dodecyl glucoside, so that the above three substances are cross-linked and fused together. Then, the reaction conditions are adjusted to be alkaline, and dopamine hydrochloride polymerizes into polydopamine under alkaline conditions and cross-links with the above components to obtain the adhesion promoter; the adhesion promoter is coated on the surface of the PP synthetic paper, and the adhesion promoter reacts with the hydroxyl groups and carboxyl groups in the release layer, or is connected by electrostatic interaction; and the reactivity of the adhesion promoter with the adhesive layer is improved, which promotes the combination of the PP synthetic paper with the release layer and the adhesive layer; by surface etching the PET film, on the one hand, the surface roughness is increased, and on the other hand, the bonding effect with the adhesive layer is improved; by adjusting the thickness of each layer, the pressure-sensitive adhesive has good initial tack and holding tack, and by controlling the temperature of the lamination, adjusting the pressure and speed of the lamination, the high-temperature resistance effect of the pressure-sensitive adhesive composite material is improved. In Comparative Example 26, no adhesion promoter is added, the bonding strength between the adhesive layer and the PP synthetic paper decreases, the viscosity decreases, and the high-temperature resistance effect is worse than that of Example 9. In Comparative Example 27, the thickness of each layer is on the high side, the diameter of the steel cylinder is small, the lamination bending radius of the pressure-sensitive adhesive composite material is small, and the lamination effect with the small-radius curved surface is poor, resulting in a decrease in initial tack and holding tack and a decrease in high-temperature resistance performance.
[0137] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made in these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. The production process of environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material, characterized by: The production process is as follows: a 19-30 μm transparent PET film is washed with deionized water, immersed in an etching solution at 30° C. for 3-5 minutes, washed and dried to obtain an etched transparent PET film; a 10-15 μm adhesion promoter is scraped on one side of a PP synthetic paper, an isolation layer is arranged on one side of the adhesion promoter, and after fixing, an adhesive layer is scraped and filled in the gap of the isolation layer, the thickness of the isolation layer and the adhesive layer are controlled to be 10-15 μm and 36-50 μm respectively, and dried to obtain a composite PP synthetic paper; the adhesive layer of the composite PP synthetic paper is overlapped with the etched transparent PET film, and hot-pressed and laminated by a laminating machine, the laminating temperature is 80-120° C., the laminating pressure is 0.5-2 MPa, and the laminating speed is 5-20 m / min, and after cooling, cutting and packaging are performed to obtain the environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material; The PP synthetic paper is prepared from PP resin, tetrapod-shaped zinc oxide whiskers treated with chenodeoxycholic acid, polyarylsulfone treated with carboxymethyl cellulose, mica powder, glycerol monostearate and erucamide; The adhesive layer is prepared from (3-glycidyl ether propyl)-1,1,3,3-tetramethyldisiloxane, 1,4-butanediol vinyl ether, dodecenylsuccinic acid, polyvinyl alcohol, isophorone diisocyanate, carboxymethyl cellulose and dodecyl glucoside; The isolation layer is prepared from carboxylated fumed silica, polylactic acid, hydroxypropyl methylcellulose and nano zinc oxide particles.
2. The production process of the environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material according to claim 1, characterized in that: The preparation method of the PP synthetic paper is as follows: drying the PP resin at 100° C. for 3 hours; adding 100 parts of the dried PP resin into a high-speed mixer, starting stirring, and setting the stirring speed to 500 rpm; sequentially adding 5-10 parts of the tetrapod zinc oxide whiskers treated with chenodeoxycholic acid, 3-8 parts of the polyarylsulfone treated with carboxymethyl cellulose, 2-5 parts of the mica powder, 1-3 parts of the glycerol monostearate and 0.5 parts of the erucamide, and continuing stirring for 15 minutes to fully mix the materials; adding the mixed materials into a twin-screw extruder, melt-extruding and granulating, and then casting into a film and biaxially stretching to obtain the PP synthetic paper.
3. The production process of the environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material according to claim 2 is characterized by: The preparation method of the tetrapod zinc oxide whisker treated with chenodeoxycholic acid is as follows: taking a tetrapod zinc oxide whisker with an aspect ratio of 10-30, washing and drying to obtain a pre-treated tetrapod zinc oxide whisker; dissolving chenodeoxycholic acid in anhydrous ethanol to obtain a chenodeoxycholic acid solution with a mass fraction of 5%; adding the pre-treated tetrapod zinc oxide whisker to the chenodeoxycholic acid solution, wherein the mass ratio of the pre-treated tetrapod zinc oxide whisker to the chenodeoxycholic acid solution is 1:5-1:10, stirring at 300 rpm for 3 hours at room temperature, filtering the mixed solution after sufficient stirring, washing the filter residue with the anhydrous ethanol for 3 times, and finally drying in a 60°C oven for 6 hours to obtain the tetrapod zinc oxide whisker treated with chenodeoxycholic acid.
4. The production process of the environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material according to claim 2, characterized in that: The preparation method of the polyarylsulfone treated with carboxymethyl cellulose is as follows: 1 part of carboxymethyl cellulose is slowly added into deionized water to prepare a carboxymethyl cellulose aqueous solution with a mass fraction of 3%; 10 parts of polyarylsulfone are added into N-methylpyrrolidone, and stirred at a temperature of 50°C to prepare a polyarylsulfone solution with a mass fraction of 10%; the carboxymethyl cellulose aqueous solution is slowly added dropwise into the polyarylsulfone solution; the mass ratio of the carboxymethyl cellulose to the polyarylsulfone is 1:10-1:20; the mixture is stirred at a speed of 1000 rpm for 3 hours at a temperature of 80°C to obtain a mixture; the mixture is slowly poured into the deionized water, filtered, washed with the deionized water for 4 times, and finally dried to obtain the polyarylsulfone treated with the carboxymethyl cellulose.
5. The production process of the environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material according to claim 1, characterized in that: The preparation method of the adhesion promoter is as follows: add 11.4 parts of the carboxymethyl cellulose and 29.2 parts of the dodecyl glycoside to the reaction system, and simultaneously add 0.5 parts of concentrated sulfuric acid, 13.5 parts of phenylboric acid and 500 parts of deionized water, heat to 70°C, react for 4 hours, then adjust the pH to 8.5, add 11.5 parts of dopamine hydrochloride, and stir at room temperature for 24 hours to obtain the adhesion promoter.
6. The production process of the environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material according to claim 1, characterized in that: The preparation method of the isolation layer is as follows: dispersing 4.5-6.5 parts of the carboxylated fumed silica in 100 parts of anhydrous ethanol, and ultrasonically dispersing for 30 minutes to obtain a uniform fumed silica suspension; completely dissolving 8-15 parts of the polylactic acid in 500 parts of ethylene glycol diacetate to obtain a polylactic acid solution; adding 80 parts of the deionized water to 2.8-4.0 parts of the hydroxypropyl methylcellulose, and dissolving at 50° C. to obtain a hydroxypropyl methylcellulose solution; dispersing 2.4-3.6 parts of the nano zinc oxide particles in a mixed solution of 0.5 parts of sodium dodecyl sulfate and 50 parts of the deionized water, and ultrasonically dispersing for 1 hour to obtain a surface-treated nano zinc oxide dispersion; dispersing the fumed silica The suspension is slowly poured into the polylactic acid solution, and stirred at 650 rpm for 3 hours to obtain an isolation layer pre-liquid; the hydroxypropyl methylcellulose solution is added to the isolation layer pre-liquid, and stirring is continued for 2 hours to obtain an isolation layer intermediate liquid; the isolation layer intermediate liquid is rotary evaporated to 30 parts, and then 120 parts of the anhydrous ethanol are added thereto, and an isolation layer precursor is obtained by electrostatic spinning; the isolation layer precursor is immersed in the surface treated nano zinc oxide dispersion, and after immersion for 10-18 hours, it is taken out, rinsed with the deionized water for 3 times to remove the nano zinc oxide particles not bound to the surface, and then vacuum dried at 50° C. for 6 hours to obtain an isolation layer intermediate; the isolation layer intermediate is woven to form the isolation layer; The average pore size of the isolation layer is 0.05-0.2 mm; the specific surface area of the fumed silica is 350 m 2 / g, carboxyl value 0.8-2.0mmol / g.
7. The production process of the environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material according to claim 1, characterized in that: The preparation method of the adhesive layer is as follows: the reaction is carried out under nitrogen conditions, 155-168 parts of the (3-glycidyl ether propyl)-1,1,3,3-tetramethyldisiloxane and 110-120 parts of the 1,4-butanediol vinyl ether are added to 200 parts of a mixed solvent, stirred evenly, 0.1 parts of a catalyst are added, stirred for 5 minutes, heated to 100° C., and reacted for 6 hours to obtain an addition product; 128 parts of butyl acrylate and 2 parts of azobisisobutyronitrile are added to the addition product, and refluxed for 5 hours; the temperature is lowered to 80° C., and a mixed solution of 123-132 parts of dodecenylsuccinic acid and 0.05 parts of concentrated sulfuric acid is continuously added, and the mixture is slowly added within 30 minutes, and reacted at a speed of 500 rpm for 3 hours to obtain an esterification product; Add 44-60 parts of the polyvinyl alcohol and 0.01 parts of the concentrated sulfuric acid to the esterification product, heat to 90°C, and react for 4 hours to obtain an adhesive precursor; reduce the temperature of the adhesive precursor to 60°C, slowly drop 108-120 parts of isophorone diisocyanate, control the dropping time to 1.5 hours, then add 0.5 parts of triethylamine, and continue to react for 5 hours to obtain an adhesive intermediate; add 11.4-13.0 parts of carboxymethyl cellulose and 29.2-31.0 parts of dodecyl glucoside to the adhesive intermediate, and add the mixed solvent so that the total number of parts of the system is 500 parts. After reacting for 6 hours, filter the obtained product, wash with deionized water, and distill under reduced pressure to obtain the adhesive layer.
8. The production process of the environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material according to claim 7, characterized in that: The viscosity of the adhesive layer is 11000-13000 cps.
9. The production process of the environmentally friendly PP synthetic paper transparent PET bottom self-adhesive composite material according to claim 1, characterized in that: The preparation method of the etched transparent PET film is as follows: take the transparent PET film, wash the surface with the deionized water to remove dust and oil, and dry it at 80°C for 45 minutes; dissolve concentrated sulfuric acid and the dodecyl glucoside in the deionized water; the mass concentration of the concentrated sulfuric acid in the prepared etching solution is 15%, and the mass concentration of the dodecyl glucoside is 1%; soak the washed and dried transparent PET film in the etching solution at 30°C for 3-5 minutes, then take it out, rinse it with the deionized water, and dry it at 60°C for 80 minutes to obtain the etched transparent PET film.
Citation Information
Cited By
Preparation method of self-adhesive paper
CN122037816A